Differences in Calculation Time Using the Manual Calculation Method and Dental Calculator Application in the Early Childhood Oral Health Impact Scale (ECOHIS) Assessment - Lubis, Kevin Richardo; Rahmad, Yulia; Kornialia, Kornialia; Zia, Hanim Khalida; Ningrum, Valendriyani (Universitas Muhammadiyah Semarang, 2025)
Background: Dental caries in children has quite serious impacts, such as teeth becoming porous, cavities, and even breaking, causing children to experience chewing and digestive problems. Maintaining the dental health of children under five years old still depends on parents, especially on his mother because in general children under five are closer to their mothers. Knowledge is a factor that very important in the formation of a person's actions. The Early Childhood Oral Health Impact Scale (ECOHIS) is a measuring tool used to assess the impact of dental health on the quality of life of early childhood. Manually measuring the ECOHIS index often takes a long time and is prone to errors. To increase efficiency, a digital dental calculator application was developed as a digital technology-based solution for calculating the ECOHIS index.Objective: This study aims to compare the calculation time between the manual calculation method and the digital dental calculator application.Method: This type of research is a quasi experiment with a research design using a posttest only group design. The sampling technique used a convenience sampling technique totaling 70 samples professional student at RSGM Baiturrahmah that met the inclusion and exclusion criteria. Data was taken in two stages, namely manual measurements in the first week and digital measurements in the third week.Results: The average time duration for manually measuring the ECOHIS index is 88.11 seconds, while with the digital application it is only 38.31 seconds. Statistical test results show that there are significant differences between digital and manual calculations. Mann Whitney test results showed a significant difference of 0.000 (p<0.05).Conclusion: the use of a digital dental calculator can speed up the measurement of the ECOHIS index.